Role of Rosuvastatin in Preventing Risk of Cardiovascular Disease in Patients with Chronic Obstructive Pulmonary Disease (Medical Forum Monthly, 2023)
Objective: This study aims to evaluate and treat dyslipidemia in COPD patients and to calculate cardiovascular disease risk before and after treating dyslipidemia.Study Design: This prospective cohort studyPlace and Duration of Study: This study was conducted at the Pharmacology, Khyber Medical College Peshawar KMC Peshawar for eighth months started from February 2022 to October 2022.Materials and Methods: This prospective cohort study enrolls 140 COPD patients according to the inclusion/exclusion criteria. After proper consent, Body mass index (BMI), LDL/HDL ratio and AIP were calculated as per protocols and 3cc blood was withdrawn from each patient to calculate lipid profile. Patients having dyslipidemia were treated with rosuvastatin 10mg and were followed for 12 weeks. Lipid profile, LDL/HDL ratio and AIP were re-calculated post follow-up and the data were recorded and analyzed using SPSS version 22.0.Results: The mean age was 56.95 ± 10.21 years. The distribution of male and females were 39.3% and 60.7% respectively. Dyslipidemia was prevalent in 47.9% COPD patients. Based on LDL/HDL ratio, 66.4% patients were in low risk group, 31.4% were in moderate risk and 2.1% were in high CVD risk group. Atherogenic index of plasma (AIP) calculations shows that 5% patients have low CVD risk, 4.3% have intermediate while 90.7% patients have high CVD risk. Post follow-up analysis reveals significant differences in dyslipidemia (p-value 0.01), AIP categories (p-value <0.001) and LDL/HDL ratio (p-value <0.001).Conclusion: COPD patients are at high risk of developing CVDs due to dyslipidemia. Management of dyslipidemia successfully reduced CVD risk in COPD patients and subsequently results in the reduction of CVD related morbidity and mortality.